The Role Of Training Strategy In The Development Of Emotional Intelligence "Field Study On Administrative Staff At Tishreen University" - Ali Dib, Kinda (Latakia University Journal - Economic and Legal Sciences Series, 2020)
The aim of this research is to determine the extent to which Tishreen University adopts the training strategy (identifying training needs, identifying resources, identifying requirements for work, identifying permanent staff). Determine the availability of the dimensions of emotional intelligence among the administrative staff in the university (self-awareness, empathy, social skills). In addition to the study of the relationship between the training strategy and the development of emotional intelligence of administrative staff. The research sample was based on the descriptive method, and the research community included all administrative staff at Tishreen University. The research sample is a soft sample of (150) administrative workers. The questionnaire was distributed to them, and (143) questionnaires were returned. Response was (95.33%). The research concluded that Tishreen University adopts the training strategy, and the dimensions of emotional intelligence are highly available to the administrative staff in Tishreen University, in addition to a significant correlation between the training strategy and the development of each dimension of emotional intelligence. هدف البحث إلى تحديد مدى تبني جامعة تشرين لاستراتيجية التدريب (تحديد احتياجات التدريب، تحديد الموارد، تحديد المتطلبات للعمل، تحديد العاملين الدائمين). وتحديد مدى توافر أبعاد الذكاء العاطفي لدى العاملين الإداريين في الجامعة (الوعي بالذات، التعاطف، المهارات الاجتماعية). بالإضافة إلى دراسة العلاقة بين استراتيجية التدريب وتنمية الذكاء العاطفي لدى العاملين الإداريين. اعتمد البحث على المنهج الوصفي التحليلي، وشمل مجتمع البحث جميع العاملين الإداريين في جامعة تشرين، أما عينة البحث فهي عينة ميسرة بلغت (150) عامل إداري، تمّ توزيع الاستبانة "أداة البحث" عليهم، وأعيد منها (143) استبانة كاملة وصالحة للتحليل الإحصائي، وبنسبة استجابة بلغت (95.33%). توصل البحث إلى أنّ جامعة تشرين تتبنى استراتيجية التدريب، كما تتوافر أبعاد الذكاء العاطفي بدرجة كبيرة لدى العاملين الإداريين في جامعة تشرين، بالإضافة إلى وجود علاقة طردية ذات دلالة معنوية بين محاور استراتيجية التدريب وتنمية كل بعد من أبعاد الذكاء العاطفي.